Cultivation theory: The effects of prolonged exposure to k-idol on impressions of k-culture among Malaysian university students - Yap, Si En (2023)
In the digital era, widespread social media adoption has fuelled Malaysian university students' interest in K-culture, resulting in the adoption of K-idols' fashion, the purchase of endorsed products, and financial and academic consequences. Therefore, this research aims to explore how extended exposure to K-idols influences the perceptions of K-culture among Malaysian university students. By examining the links between students' views of K-idols and their perspectives on Kculture, this research sheds light on the impact of media consumption and the evolving dynamics of cross-cultural influence. This quantitative research utilised a Likert scale questionnaire distributed to Malaysian university students via Google Forms, with a sample size of 50 students. The analysis uncovers a significant connection between K-idols and university students' growing interest in various aspects of K-culture. Interestingly, even with exposure falling short of the "heavy viewer" criteria as per Cultivation Theory, modest exposure to K-idol media content significantly shapes beliefs and attitudes. The research finds that K-idols' influence extends to cultural exchange and globalisation, enriching university students' understanding of K-culture. Furthermore, the research reveals that K-culture holds a stronger appeal for respondents compared to other cultural elements, highlighting the profound impact of K-idol media content on Malaysian university students' perceptions.